Dolichopodidae (Diptera) from the Iberian Peninsula, with description of three new species - Naglis, Stefan; Barták, Miroslav (Zootaxa, 2015)
Faunistic data is given for 43 species of Dolichopodidae from the Iberian Peninsula. Altogether nine species are recorded for the first time from Portugal and six species from Spain. Three species are described as new to science: Chrysotimus meridionalis sp. nov. (Spain, Portugal), Hercostomus ibericus sp. nov. (Spain), and Sciapus negrobovi sp. nov. (Portugal).